HUME'S SECOND THOUGHTS ON PERSONAL IDENTITY. - Sunny Yang (Problems / Problemos, 2018)
In this paper, I present an interpretation on how Hume can escape from his intellectual ordeal concerning personal identity in the Appendix of the Treatise. First of all, I present the source of Hume's despair to offer an interpretation on what would have truly bothered Hume in the Appendix, and I identify several lines of interpretation. Recently Jonathan Ellis has distinguished various ways of understanding Hume's predicament. Of the four groups of explanations that Ellis distinguishes, in this paper I elaborate on the three that Ellis does not sufficiently explicate, addressing some key issues that Ellis missed. Last, I offer an alternative reading of Hume's difficulty, based on Dennett's ideas on the matter, and make a suggestion about what Hume ought to have said about these problems.